Variasi Tekstur Serpentinisasi Lherzolit dan Harzburgit Ofiolit Banggai: Implikasi Petrogenesis dan Evolusi Mantel - Alifia Widya Warapsari Badaru; Ni Luh Ananda Pusvita Sari; Mohamad Sayid Rahmat; Mohammad Ridho Paudi; Moh Fadlyansyah T (Universitas Negeri Gorontalo, 2025)
Serpentinized ultramafic rocks from the Banggai Ophiolite Complex, part of the East Sulawesi Ophiolite Belt in Central Sulawesi, preserve important records of geodynamic history and fluid-rock interaction in oceanic lithosphere. This study analyzes mineral composition, serpentinization textures, and petrogenetic implications of three drill core samples from borehole NA2, Banggai Regency. The study aims to characterize lithological and serpentinization texture variations across different peridotite types. Petrographic analysis was performed on thin sections using polarizing light microscopy; rock classification used the Streckeisen ultramafic rock classification diagram. Two samples were identified as serpentinized lherzolite with olivine content 35-40%, orthopyroxene 14-15%, clinopyroxene 13-20%, and one sample as serpentinized harzburgite with very high orthopyroxene (38%) and very low clinopyroxene (5%). Three serpentinization textures were identified: mesh texture after olivine in all three samples, bastite texture after pyroxene in one lherzolite only, and cataclastic texture in the second lherzolite only. The heterogeneous texture distribution indicates local structural control on serpentinization rather than uniform pervasive alteration. Clinopyroxene depletion contrasts between lithologies reflect heterogeneous partial melting degrees within a single ophiolite mantle segment.